Intestinal lactase, sucrase, and alkaline phosphatase in 373 patients with coeliac disease. Issue 3 (March 1984) - O'Grady, J G; Stevens, F M; Keane, R; Cryan, E M; Egan-Mitchell, B; McNicholl, B; McCarthy, C F; Fottrell, P F
Abstract : Lactase, sucrase, and alkaline phosphatase activities were measured in 833 peroral small intestinal biopsies from 373 patients with coeliac disease. Enzyme activities decreased with increasing degrees of mucosal damage. Enzyme activities in mucosae of patients with coeliac disease in remission were lower than in control groups matched for age, sex, and site of biopsy. Enzyme activities were measured in 81 patients when the mucosa was severely damaged and later when considerable improvement had occurred. Lactase activity remained low in 13% of patients under the age of 18 and in 33% of those over 18 years. Sucrase activity usually improved with histological recovery, but alkaline phosphatase activity tended to remain depressed in patients in whom lactase activity failed to improve.